Analisis pemahaman konsep peserta didik menggunakan instrumen four-tier diagnostic test - Yulianty, Sindanita; Utami, Noviani; Zulkarnaen, Zulkarnaen (Jurnal Kajian Pendidikan IPA, 2025)
Analysis of students' concept understanding using a four-tier diagnostic test instrument. This research is related to the understanding of student concepts that are adjusted to the four-level diagnostic test instrument. Then the understanding of the concept being studied is explained in detail into sub-concepts. The aim of this study is to determine students' understanding of the conceptof the development of ectoderm into its derivatives concept. The research method used is descriptive quantitative. The instrument used to measure students' understanding of concept is a diagnostic assessment in the form of a four-tier diagnostic test instrument. The four-tier diagnostic test instrument consists of 20 multiple-choice compound questions. Each question consists of 4 levels: the first level is related to the main question, the second level is related to the student's confidence in the first question, the third level is related to the reasons for the answer to the first question, and the fourth level is related to the student's confidence in the third question. The results of this study are that the sub-concepts that students have not mastered yet are the germinal layers with the highest average percentage of misconceptions (42.46%) and the lowest average percentage of scientific knowledge (28.57%). The sub-concept that students have mastered the most is the sub-concept of the development of ectoderm into epidermis with the second lowest average percentage of misconceptions (18.25%) and the highest average percentage of scientific knowledge (71.53%). In the false negative, false positive, and lack of knowledge criteria, the average percentage isthe low category for all sub-concepts. Due to this, a small number of students are still confused in understanding the concept of the development of ectoderm into its derivatives. However, there are still students who experience misconceptions, so improvements are needed to the learning mechanism. Improvements can be made to the learning methods used. Keyword: descriptive quantitative, diagnostic test, four-tier diagnostic test, misconception